2014
DOI: 10.1038/ki.2013.527
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for intraluminal colonization of hemodialysis catheters?

Abstract: Hemodialysis catheter-related bloodstream infections are potentially devastating, leading to increased morbidity, mortality, and cost of care. Prospective studies published over the past 15 years shed light on the pathogenesis of these infections. The data suggest that the intraluminal microbial colonization of hemodialysis catheters often precedes bloodstream infection. This finding supports strategies aimed at preventing or eradicating intraluminal colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…In addition, repeated exposure of microorganisms to such a lock solution would be predicted to have a cumulative effect. Exposure times may often be increased from what we have tested here (i.e, hemodialysis patients for 24 to 72 h [ 17 ], oncology patients for 24 h to 3 weeks [ 8 ], and total parenteral nutrition patients for 12 to 24 h [ 66 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, repeated exposure of microorganisms to such a lock solution would be predicted to have a cumulative effect. Exposure times may often be increased from what we have tested here (i.e, hemodialysis patients for 24 to 72 h [ 17 ], oncology patients for 24 h to 3 weeks [ 8 ], and total parenteral nutrition patients for 12 to 24 h [ 66 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Harsh conditions for microorganisms within a CVAD would include mechanical flushing and the use of antibiotic agents ( 6 ). Each time the CVAD is used, there is potential for resistant microorganisms sloughing off from a biofilm and entering the patient’s bloodstream ( 6 , 11 , 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because filling the dialysis catheter with citrate solution can prevent only intraluminal colonization, it is unclear why we observed a significant reduction of catheter-tip colonization in our study. The first hypothesis is that, similarly to long-term dialysis catheters (20,21), the intraluminal route of catheter-tip colonization may predominate for shortterm dialysis catheters in the ICU population due to frequent manipulations of the catheter hub or connectors and possibly the choice of the locking solution (22). Additional studies on the dynamics of catheter colonization are warranted in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis patients with CVCs have significantly higher C-reactive protein and markedly lower serum albumin concentrations, both of which are biomarkers of inflammation with strong associations with mortality in the hemodialysis population ( 3 , 4 ). Several studies have shown that CVCs are rapidly colonized after insertion with Gram-positive organisms that can form intraluminal biofilm which can be a source of inflammation if planktonic bacteria or biofilm fragments enter the systemic circulation ( 5 ). Bosma et al evaluated 32 newly placed CVCs and showed that 30 days after catheter insertion, 100% had biofilm formation when examined by scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, semiquantitative measurement of LTA has been investigated as a bioassay to detect early Gram-positive blood stream infections ( 10 ). However, in hemodialysis patients and other populations requiring longer-term CVC use, inflammation induced by dissociated intraluminal biofilm fragments likely precedes infection ( 5 ). There are currently no published studies that have quantified LTA in the catheter aspirate and systemic circulation of patients with CVCs.…”
Section: Introductionmentioning
confidence: 99%